Phase II study of the efficacy and safety of lenvatinib for anaplastic thyroid cancer (HOPE). (September 2022) - Higashiyama, Takuya; Sugino, Kiminori; Hara, Hisato; Ito, Ken-ichi; Nakashima, Noriaki; Onoda, Naoyoshi; Tori, Masayuki; Katoh, Hiroshi; Kiyota, Naomi; Ota, Ichiro; Suganuma, Nobuyasu; Hibi, Yatsuka; et al.
Abstract: Purpose: Anaplastic thyroid cancer (ATC) is a rare and highly aggressive cancer for which effective systemic therapy has long been sought. Here, we assessed the efficacy and safety of lenvatinib in patients with unresectable ATC. Patients and methods: The study was investigator-initiated and conducted under a multicenter, open-label, nonrandomized, phase II design. Eligibility criteria included pathologically proven ATC; unresectable measurable lesion as defined by RECIST 1.1; age 20 years or older; ECOG PS 0–2; and adequate organ function. The primary end-point was overall survival. Secondary end-points were progression-free survival, objective response rate, disease control rate, clinical benefit rate, and safety. Results: Of 52 patients enrolled from 17 institutions, 42 patients who were confirmed to have ATC were included for efficacy analysis, and 50 patients were included for safety analysis. The estimated 1-year overall survival rate was 11.9% (95% CI, 4.4%–23.6%). One patient (2.4%) achieved complete response, four patients (9.5%) partial response, and 26 patients (61.9%) stable disease, including nine patients (21.4%) who demonstrated durable stable disease, giving an objective response rate of 11.9%, disease control rate of 73.8%, and clinical benefit rate of 33.3%. Adverse events of any grade were observed in 45 patients (90.0%), the most common of which of any grade included loss of appetite (48.0%), fatigue (48.0%), hypertension (44.0%), and palmar-plantar erythrodysesthesia syndrome (26.0%). Conclusion: Lenvatinib treatment resulted in disappointing survival for unresectable ATC patients. Although the number of responders was small, responses were durable, indicating that lenvatinib may be beneficial for selected patients. Further investigation to identify suitable candidates for lenvatinib monotherapy is needed. Highlights: This study assessed the efficacy and safety of lenvatinib in unresectable ATC. The estimated 1-year overall survival rate was 11.9%. The estimated 1-year progression free survival rate was 4.9%. The objective response rate was 11.9%, and the disease control rate was 73.8%. No fatal haemorrhagic side-effect was observed.